“Death or Freedom”: Transformation of Household Plots into Political Ones. On the material of the hidden Ukrainian state coat of arms on embroidered Ukrainian towels (rushnyks) - Brovarets, Tetiana (Eikón / Imago, 2026)
This article is devoted not only and not so much to the presence of national symbols (in particular, the trident which is the state coat of arms of Ukraine) on century-old Ukrainian rushnyks (embroidered towels). The main goal of this study is to show how closely the so-called political (patriotic) may be intertwined with household (everyday) embroidered plots, that we can sometimes easily confuse them. Since it was dangerous to embroider Ukrainian national symbols during the occupation and struggle for state independence, such signs often had to be masked. Thus, such usual embroidered scenes, as entertainment and fun or separation and meeting of a boy and a girl, could hide political undertones. And vice versa, using the ready-made printed cross-stitch papers containing the state coat of arms of Ukraine, girls sometimes could avoid embroidering this sign.